2023
DOI: 10.1158/1078-0432.ccr-22-3736
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Profiling of Metastatic Castration-Resistant Prostate Cancer Samples Resistant to Androgen Receptor Pathway Inhibitors

Abstract: Purpose: The androgen receptor axis inhibitors (ARPI) (e.g, enzalutamide, abiraterone acetate) are administered in daily practice for men with metastatic castration-resistant prostate cancer (mCRPC). However, not all patients respond, and mechanisms of both primary and acquired resistance remain largely unknown Experimental Design: In a prospective trial MATCH-R (NCT02517892), 59 mCRPC patients underwent whole exome sequencing (WES) and/or RNA-sequencing (RNA-seq) of samples collected before starting ARPI. Als… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 51 publications
0
0
0
Order By: Relevance
“…The percentage of genes participating directly or indirectly in the AR activity increased from 47% for those shared between MP1 and MP2 (7 over 15 genes) to 78% (7 over 9 genes) for genes common to PCa-and CRPCgene lists. These results confirmed the essential role of AR in regulating PCa cells growth and proliferation during the early stages of the oncogenesis, as well as in the resistance acquisition [3,74]. It has been reported that the anti-androgen therapy pressure exerted on the intrinsic cellular heterogeneity of PCa tissues led to the selection of tumour cells showing AR gene alterations or epigenetic perturbation of its regulated pathways [8,11].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The percentage of genes participating directly or indirectly in the AR activity increased from 47% for those shared between MP1 and MP2 (7 over 15 genes) to 78% (7 over 9 genes) for genes common to PCa-and CRPCgene lists. These results confirmed the essential role of AR in regulating PCa cells growth and proliferation during the early stages of the oncogenesis, as well as in the resistance acquisition [3,74]. It has been reported that the anti-androgen therapy pressure exerted on the intrinsic cellular heterogeneity of PCa tissues led to the selection of tumour cells showing AR gene alterations or epigenetic perturbation of its regulated pathways [8,11].…”
Section: Discussionsupporting
confidence: 79%
“…The significant efforts made to study the molecular mechanisms involved in PCa progression identified molecular alterations potentially relevant for improving the clinical management of patients [73,74]. Over the past decade, the use of new drugs inhibiting the AR axis improved the treatment of mPCa and some forms of CPRC, but these chemicals have led to increased CRPC with neuroendocrine features that are still incurable [3,51].…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] About 80% of the time, castration resistance is dependent upon reacquired androgen receptor signaling. 9,10 Several resistance mechanisms exist, including AR amplification and mutation, expression of constitutively active AR splice variants such as AR-V7, GR-mediated bypass, and increased endogenous autocrine or paracrine-mediated androgen availability. [11][12][13][14][15][16][17][18] In addition, lineage plasticity relieves a requirement for AR signaling, and is associated with loss of AR expression, rendering tumor cells unresponsive to androgen blockade, resulting in the development of neuroendocrine prostate cancer (NEPC), and double-negative prostate cancer.…”
Section: Introductionmentioning
confidence: 99%